Bare and protein-conjugated Fe3O4 ferromagnetic nanoparticles for utilization in magnetically assisted hemodialysis: biocompatibility with human blood cells - Stamopoulos, D.; Manios, E.; Gogola, V.; Benaki, D.; Bouziotis, P.; Niarchos, D.; Pissas, M. (NANOTECHNOLOGY, 2008)
Magnetically assisted hemodialysis is a development of conventional hemodialysis and is based on the circulation of ferromagnetic nanoparticle-targeted binding substance conjugates (FN-TBS Cs) in the bloodstream of the patient and their eventual removal by means of a 'magnetic dialyzer'. Presented here is an in vitro investigation on the biocompatibility of bare Fe3O4 FNs and Fe3O4-bovine serum albumin Cs with blood cells, namely red blood cells (RBCs), white blood cells (WBCs) and platelets (Plts). Atomic force microscopy (AFM) and optical microscopy (OM) enabled the examination of blood cells at the nanometer and micrometer level, respectively. The observations made on FN- and C-maturated blood samples are contrasted to those obtained on FN- and C-free reference blood samples subjected to exactly the same maturation procedure. Qualitatively, both AFM and OM revealed no changes in the overall shape of RBCs, WBCs and Plts. Incidents where bare FNs or Cs were bound onto the surface of RBCs or internalized by WBCs were very rare. Detailed examination by means of OM proved that impaired coagulation of Plts is not initiated/promoted either by FNs or Cs. Quantitatively, the statistical analysis of the obtained AFM images from RBC surfaces clearly revealed that the mean surface roughness of RBCs maturated with bare FNs or Cs was identical to the one of reference RBCs.